Comparison of Intraocular Lens Calculation Formulas for Phacoemulsification after Corneal Refractive Surgery in Asian Eyes - Cris Martin Jacoba, MD, DPBO; Mary Ellen Sy, MD, DPBO; Isa Mulingbayan Jacoba, MD (Philippine Journal of Ophthalmology)
Objective: To compare the different intraocular lens (IOL) calculation formulas available on the American Society of  Cataract and Refractive Surgery (ASCRS) IOL power calculator website among Asian eyes with previous corneal refractive surgery.